KRAS Mutations in Papillary Fibroelastomas: A Study of 50 Cases With Etiologic and Diagnostic Implications. (May 2020) - Bois, Melanie C.; Milosevic, Dragana; Kipp, Benjamin R.; Maleszewski, Joseph J.
Abstract : Papillary fibroelastoma (PFE) is an increasingly recognized cardiac tumor. Despite its prevalence, controversy exists as to whether it represents a reactive or neoplastic process due to histopathologic similarities with Lambl excrescences (LEs), an accepted reactive phenomenon. Recently, KRAS mutations were reported in a small collection of PFEs, but the incidence of mutations and conditions in which they arise in are unknown. Furthermore, the relationship between PFE and LE has yet to be investigated. Institutional archives were queried for cases of PFE (2001-2017). Paraffin-embedded tissue was microdissected for tumor isolation. Prospectively identified LEs (2018) were collected and wholly isolated. Extracted DNA underwent droplet digital polymerase chain reaction analysis of the most common KRAS mutations (codons 12/13 and 61). Relevant clinical information was abstracted from the medical record. Fifty-two PFEs were tested from 50 patients (32 women). The median patient age was 67 years. Seventeen (33%) PFEs harbored pathogenic variants in tested KRAS codons (12 in codons 12/13; 5 in codon 61). Mutations were mutually exclusive. No clinical or pathologic correlates differed significantly from cases without detectable pathogenic variants. No pathogenic mutation were detected in LEs (n=20; P =0.002). Herein, we report on the largest series of PFE tested for KRAS mutations and present the largest cohort of KRAS -mutant PFEs to date, providing evidence in support of the notion that at least a subset of PFEs represents neoplasia. Moreover, the lack of KRAS mutations in LEs provides evidence as to the separate etiology of this accepted reactive lesion. Abstract : Supplemental Digital Content is available in the text.